2019
DOI: 10.1007/978-3-030-15742-5_12
|View full text |Cite
|
Sign up to set email alerts
|

“Autsome”: Fostering an Autistic Identity in an Online Minecraft Community for Youth with Autism

Abstract: Autism is a medical diagnosis that has attracted much attention in recent decades, particularly due to an increase in the numbers of children being diagnosed and the changing requirements for getting the diagnosis. In parallel online communities around autism-both those supporting individuals, families seeking treatment and those supporting embracing the autism identity-have grown. Previous literature has shown the positive impact support groups can have for those encountering hardship in their lives, such as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…Many recent research studies have indicated that Autcraft offers neurodiverse players a safe space to participate in positive and meaningful play that integrates social and sensory experiences [82][83][84][85][86][87]. Some specifically reported that the use of speech during the reciprocal conversation (e.g., request, command, initiation) to build friendship and share game experiences further extends positive learning and intervention outcomes [85][86][87].…”
Section: Autcraftmentioning
confidence: 99%
See 3 more Smart Citations
“…Many recent research studies have indicated that Autcraft offers neurodiverse players a safe space to participate in positive and meaningful play that integrates social and sensory experiences [82][83][84][85][86][87]. Some specifically reported that the use of speech during the reciprocal conversation (e.g., request, command, initiation) to build friendship and share game experiences further extends positive learning and intervention outcomes [85][86][87].…”
Section: Autcraftmentioning
confidence: 99%
“…In this virtual environment, players can manipulate particles with different shapes, sizes, and densities to visualize the abstract concept of "social distancing," which can be difficult and risky to teach in a real-world learning environment (e.g., public spaces such as school, museums, and libraries) during a global pandemic. This example demonstrated how an adult stakeholder leveraged the Autcraft platform, reappropriated the conventional play interaction of "building with particles," and offered direct supports to create embedded learning and inclusive play opportunities for neurodiverse players [82][83][84][85][86]91].…”
Section: Autcraftmentioning
confidence: 99%
See 2 more Smart Citations
“…As seen in, e.g., the game Minecraft with assumptions made on different levels of completion [100%](Ringland 2019), or in choices of colors as potential signs of depression. 11 Player categorization according to Bartle's taxonomy: killer, achiever, socializer, explorer, see e.g.…”
mentioning
confidence: 99%